Characterizing the constitutive response of plain-woven fibre reinforced aerogel matrix composites using digital image correlation. (15th February 2020) - Ji, Xiaohui; Hao, Ziqing; Su, Lijun; He, Tiren; Liu, Liu
Highlights: Stress-strain constitutive parameters of composites are extracted by DIC method. Nonlinear coupling of stress-strain occurs under a complex in plane stress state. High order terms of stress components are included in the constitutive model. Abstract: The paper presents an experimental investigation of the constitutive behavior for plain-woven fibre reinforced silica aerogel matrix composites under a complex in-plane stress state using digital image correlation technique. Specimens were subjected to in-plane on-axis, off-axis tension and shear loadings. The material exhibits significantly nonlinear stress-strain behaviour under off-axis tension and shear loadings. Deformation mechanism of the composite material has been proposed using FEM analysis of representative volume cell qualitatively. It is proposed that nonlinear couplings of the stress and strain components may result from a combination of stress-free surface, heterogeneity and interaction of the woven fibre bundles and aerogel matrix for thin specimen under a complex stress state, even though no damage initiates in the material. The experimental results were subsequently used to develop a constitutive model based on general formulation of complementary strain energy density. The material constitutive parameters were extracted from calculated stress and measured strain using multi-variable linear least square regression. The performance of the constitutive model has been demonstrated by comparison with the off-axis tensile experimental results.